PERMASALAHAN MENARCHE DINI (TINJAUAN HUKUM ISLAM TERHADAP KONSEP MUKALLAF) - Jayusman Jayusman (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Early menarche or first menstruation in women earlier than usual is an interesting problem to be studied and investigated further. Changes in life style and increase in social welfare impact on rapid physical growth of children and then result on the shift of age of menarche. Physically, they have growth like adult but psychologically they are children. In another word, they are children trapped in the body of adult. In the perspective of Islamic law, women experiencing menstruation is considered entering the age of maturity. As adult, she imposes religious obligation and is responsible for her acts while in fact she is a child. This is among problems of women and their feminine problem. Allegedly, many people do not understand this matter and thus allowing confusion. Therefore, this issue needs to be discussed form Islamic point of view.Keyword: menarche, menstruation